Venous Stent Migrating to the Right Heart Causing Severe Regurgitation. (November 2020) - Khalid, Mazin O.; Moskovits, Norbert; Frankel, Robert A.; Moskovits, Manfred; Saunders, Paul C.; Jacobowitz, Israel J.; Ribakove, Greg H.; Shani, Jacob
Venous stent migration to the cardiopulmonary system is a rare but serious complication. Cardiopulmonary involvement has various presentations such as valvulopathy, acute heart failure, arrhythmias, endocarditis, and tamponade. The presenting symptoms depend on the eventual location of the stent in the heart or lungs, size of the stent, and valve involvement. Extracardiac dislodgement can be managed by catheter-directed extraction or proper deployment within the containing vessel or surgical extraction. Intracardiac stents may require open surgery to prevent life-threatening complications. We present an asymptomatic patient with stent migration that lead to severe tricuspid regurgitation and required tricuspid valve replacement